In Madhya Pradesh... Scientific papaya cultivation changing life style - Tyagi, S. K.; Sharma, M. L.; Khire, A. R. (Indian Horticulture, 2019)
The joint efforts of scientists and Rakesh Patidar resulted in a big success in 2008- 09, increasing his income to `11,90,000 from 2.42 ha of land. The rising graph of income recorded as `15,00,000/ and 21,50,000/ in subsequent years of 2010-11 and 2011-12 with the land of 2.82 ha and 4.04 ha, respectively.